Moving Public Opinion by Politicians: Action Study #AyoMoveOn2024 Through Social Media X - Zitri, Ilham; Kurniawan, Cahyadi; Rifaid, Rifaid (Universitas Pancasakti, 2025)
The use of social media as a channel for political communication has an influence in determining a person's political behavior, so that it can form public opinion among the community. The reason X is called an information disseminator is because most of the trending topic hashtags that are trending on X become headlines. This is due to the power of X as a mouthpiece for conventional media news, so that many people use it, especially politicians. Therefore, it is not surprising that public opinion is easily formed and is often found on social media X. X is a form of social media that allows its users to express their opinions on various topics effectively. The focus of this study is how politicians influence public opinion. This study explores the intensity of conversations on the @fahrihamzah account and issues related to the #AyoMoveOn2024 action on social media. This study uses a qualitative method with the Qualitative Data Analysis (QDA) Miner approach, which helps network, content, and cloud analysis using Nvivo 12 Plus software. The results of this study indicate that being a consistent medium for spreading public opinion campaign actions through the @Fahrihamzah account network through the #AyoMoveOne2024 public opinion campaign with high conversation intensity. In addition, public opinion accompanying the #AyoMoveOn2024 action campaign shows that the Geloraid party made the most mentions with an intensity of 12.70%. Then the most prominent hashtag is #ayomoveon2024, with an intensity of 10.34%. Furthermore, there were 3013 tweets sent by the @Fahrihamzah account in the #AyoMoveOn2024 action, with seven retweets. This study can illustrate how social media X is effective as a means of disseminating information and campaigning for action by X social media users.